Temporal characteristics of stable isotopes of oxygen ( 18 O) and hydrogen ( 2 H) at Senai, Johor, Malaysia - Ninu Krishnan MV; Yusri Yusup; Punyawi Jamjareegulgarn; H. Vijith (Isotopes in Environmental and Health Studies, 2025)
O and δD isotopes is deemed crucial as essential climate response variables. This research will enhance our understanding of the hydrological cycle and improve predictions regarding the impacts of future climate change and alterations in ecosystems.
Keywords: Groundwater and Isotope Geochemistry; Isotope Analysis in Ecology; Radioactivity and Radon Measurements